Influence of Solid–Liquid Two-Phase Flow on Cavitation of Tubular Turbine Blades Under Combined Conditions - Cheng, Chuang; Li, Zhenggui; He, Fubing; Wu, Siyuan; Zeng, Chuchu; Zhang, Kui; Zheng, Jing (Frontiers in Energy Research, 2022)
The influence of sediment media on the blade pressure and cavitation of a tubular turbine was investigated in this study. The Zwart–Geber–Belamri cavitation model and the shear stress transport k–w turbulence model were applied to numerically simulate and experimentally validate the full flow path of the tubular turbine under combined conditions for sediment particle sizes of 0.01 and 0.05 mm and concentrations of 1%, 1.5%, and 2%. The results show that the pressure of the blade increases with the sediment concentration. Cavitation mainly occurs between the blade shroud and the leading edge. The higher the sediment concentration, the lower the vapor volume fraction at the same sediment particle size. The presence of sediments inhibits further cavitation development, and the inhibition effect is significant. At the same concentration, the larger the particle size of the sediment, the lower the vapor volume fraction. Thus, the increase in the particle size inhibits cavitation, but the inhibition effect is not significant.